Additional Role of Magnetic Resonance Imaging to Ultrasound in Assessing Placenta Accreta Spectrum Disorders: A Retrospective Cross-sectional Study from Vietnam - Viet Hung Nguyen; Quang Huy Huynh; To Nguyen Ha; Minh Chau Ngoc Nguyen; Phuc Nhon Nguyen (Oman Medical Journal)
Objectives: Placenta accreta spectrum (PAS) is commonly associated with adverse pregnancy outcomes. While ultrasound (US) is the primary imaging tool, magnetic resonance imaging (MRI) plays a crucial complementary role in assessing PAS disorders. This study aimed to evaluate the MRI features in PAS diagnosis and enhance the role of MRI in conjunction with US for better management. Additionally, the study examined the association between imaging findings and clinical outcomes. Methods: This retrospective cross-sectional study was conducted between January 2017 and June 2022 at Tu Du Hospital, Vietnam. A total of 87 cases were eligible for inclusion. Antenatal MRI and US findings were compared to intraoperative diagnoses and/or histopathological confirmation, which is considered the gold standard. The diagnostic value of each MRI feature was calculated, and the association between MRI/US findings, estimated blood loss, and surgical methods was analyzed. Statistical significance was determined with a p-value < 0.05. Results: Among the 87 women suspected of PAS on US, 83 were confirmed to have PAS through intraoperative diagnosis and/or histology. The mean maternal age was 35.9 ± 5.7 years and the mean gestational age at cesarean section was 31.1 ± 7.1 weeks. MRI sensitivity (Se) in detecting PAS ranged from 10.8–94.0%, while the specificity (Sp) ranged from 25.0–100%. Loss of retroplacental T2 dark zone demonstrated the highest diagnostic value. When combining three to six MRI signs, Se increased from 53.0–100%, and Sp from 25.0–100%. The highest Youden’s index (0.759) was observed with five MRI signs (Se = 75.9%, Sp = 100%). PAS diagnosed via MRI/US was associated with more significant blood loss during cesarean section (1000 (600–2000) mL vs. 500 (250–850) mL and 1000 (600–2000) mL vs. 300 (300–500) mL, respectively). Furthermore, the percreta type of PAS identified on MRI/US was linked to significantly higher rates of cesarean hysterectomy compared to conservative surgery (56.4% vs. 43.6% and 63.5% vs. 36.5%, respectively). Conclusions: MRI provides a reliable diagnostic value for PAS, particularly following uncertain US findings. Depending on resource availability, a stepwise approach utilizing both imaging modalities should be considered. MRI can guide strict interdisciplinary management in cases of suspected PAS, especially percreta type. Further studies are needed to solidify the role of MRI in severe PAS cases.